1982
DOI: 10.1002/bdd.2510030408
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent pharmacokinetics of furosemide in the rat

Abstract: The pharmacokinetics of furosemide were investigated in the rat at doses of 10 and 40 mg kg-1 corresponding to doses of 80 and 320 mg given to humans based on body surface area. A three-compartment open model with renal excretion taking place from the shallow peripheral compartment gave the best fit to the data. The terminal half-life of furosemide was found to change from 29 min for the 10 mg kg-1 dose to 49 min for the 40 mg kg-1 dose. This change could be detected as a change in the apparent volume of distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 20 publications
(5 reference statements)
2
16
0
Order By: Relevance
“…The affinities of warfarin and phenylbutazone for RSA (K a = 8.3 × 10 5 M −1 , and 4.6 × 10 5 M −1 ), respectively, and HSA (K a = 3.4 × 10 5 M −1 , and 7.0 × 10 5 M −1 ), respectively, are nearly identical 45. An affinity constant for furosemide binding to RSA has not been reported, however, one study reported furosemide binding to RSA as high as 99.1% 46. As observed with HSA, warfarin, phenylbutazone, and furosemide were able to competitively displace [ 64 Cu]Cu-PTSM from protein binding sites in rat serum (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…The affinities of warfarin and phenylbutazone for RSA (K a = 8.3 × 10 5 M −1 , and 4.6 × 10 5 M −1 ), respectively, and HSA (K a = 3.4 × 10 5 M −1 , and 7.0 × 10 5 M −1 ), respectively, are nearly identical 45. An affinity constant for furosemide binding to RSA has not been reported, however, one study reported furosemide binding to RSA as high as 99.1% 46. As observed with HSA, warfarin, phenylbutazone, and furosemide were able to competitively displace [ 64 Cu]Cu-PTSM from protein binding sites in rat serum (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…administration, the plasma levels of furosemide declined polyexponentially with significantly higher levels in AIDRs than those in control rats (Figure 1), and this resulted in a significantly higher AUC (4280 versus 3190 mg min mL − 1 ) in AIDRs ( (Table 1). Since it has been reported that the Cl of furosemide was dose [31] or concentration [32] dependent in rats, and Cl r of furosemide was urine flow-dependent in rabbits [33], the values of Cl, Cl r , and Cl nr listed in Table 1 were time-averaged values. The amount (2280 versus 3760 mg) and percentages of i.v.…”
Section: Resultsmentioning
confidence: 99%
“…The rat was placed in a cage with a track through which the fistula protruded, and it could move freely along the track. This catheterisa tion allowed exact samples of both blood and urine to be collected at exact times, and without unneces sary stress on the rat [Hammarlund and Paalzow, 1982], The rat was allowed to rest during 1 day (day 2) after the surgical procedure, and the normal uri nary output was measured. Endogenous creatinine clearance was estimated on the experimental day (day 3) as a measurement of the physical condition of the kidneys.…”
Section: Renal Excretionmentioning
confidence: 99%
“…The hepatic elimination of probenecid was studied by an in vitro liver perfusion technique [Hems et al, 1966] and the renal excretion in vivo by catheterization of the urinary bladder [Hammarlund and Paalzow, 1982],…”
Section: Introductionmentioning
confidence: 99%